BUSINESS INTELLIGENCE AND VALUE CREATION BY SELECTED BANKS IN SUB-SAHARAN AFRICA: TECHNOLOGICAL, ORGANISATIONAL, AND ENVIRONMENTAL THEORY - (:unkn) unknown (My University, 2022)
As the demand for the quantification of the association between business intelligence and value creation continues to gain momentum, this parametric study empirically tests the relevance of technology-organisation-environment (TOE) theoretical framework on the correlation between business intelligence and value creation using data from the biggest banks in Ghana, Nigeria, and South Africa in terms of total assets. While Nigeria and South Africa are the two largest economies in Africa, Ghana is one of the pacesetters in parliamentary democracy in Africa since 1992. GBC Bank Ghana limited, Access Bank of Nigeria Plc, and Standard Bank of South Africa Limited are the three banks that made the study. Hardware and software proxied business intelligence technology, bank size proxied organisation, total deposit proxied environment, and value creation is measured with value added by the sampled banks. Pearson correlation analyses were carried out with the aid of the statistical package for social sciences (SPSS). Using audited data from annual reports of the sampled banks from 2010 - 2020 (11 years); the study established that: (i) all the TOE variables have significant positive associations with value creation in Ghana, Nigeria, and the Group while they have nonsignificant positive associations with value creation in South Africa. These groundbreaking empirical findings indicate the overall relevance of the TOE theoretical framework in banks in Sub-Saharan Africa (Group results), Ghana, and Nigeria. Practically and policy-wise, the findings calls on corporate policy makers to improve on hardware and software investments as they add on to their banks’ value creation capacity. There is need for further study to test the relevance of the TOE framework in Banks in South Africa as well as other Sub-Saharan African countries.
Keywords: African Research